Chitosan-Impregnated Activated Carbon Derived from Sugarcane Bagasse for Alizarin Red S Adsorption - Dina Fitriana; Sri Hastuti; Abu Masykur; Atmanto Heru Wibowo; Puput Nursetyani; Miftahul Rohmah; Faiza Dzikra Az-Zahra (Jurnal Kimia Sains dan Aplikasi, 2025)
In the present study, a chitosan-impregnated activated carbon derived from sugarcane bagasse (Cs-Act SB) has been synthesized for the removal of Alizarin Red S (ARS) dye from an aqueous solution. The dried sugarcane bagasse sample was rinsed with 0.5% HCl to eliminate impurities and subsequently dried overnight at 110°C. Thereafter, it was subjected to carbonization in a furnace at 600°C for 2 h to produce sugarcane bagasse biochar (SB). The SB was then chemically activated using NaOH and physically activated in a muffle furnace at 750°C for 2 h to produce activated carbon (Act-SB). The obtained Act-SB was then modified using chitosan to yield Cs-Act SB biocomposite. The Act-SB and Cs-Act SB were characterized based on moisture content and ash content, pH points of zero charge (pHPZC), FT-IR, SEM-EDX, and TGA-DTA analysis. The Cs-Act SB has a moisture content of 4.0% and an ash content of 3.40%, respectively. The results show that the adsorbent process is desirable at low pH under acidic conditions (pH 2) with a pHPZC of 4.58. Based on the FT-IR spectra, the characteristic peaks of the chitosan were shown for Cs-Act SB at 3440 cm−1 due to the stretching vibration of the hydroxyl and amino functional group. The surface of Cs-Act SB has an irregular and heterogeneous surface and has high carbon content (84.42%). The TGA-DTA results showed the stability of Cs-Act SB with respect to temperature. Moreover, the adsorption kinetics were found to follow a pseudo-second-order kinetic model, and the adsorption isotherms are best described by the Langmuir model for both Act-SB and Cs-Act SB. The determined Langmuir maximum adsorption capacity of Cs-Act SB and Act-SB for the ARS dye adsorption were 78.13 mg g−1 and 30.03 mg g−1, respectively. Kinetics and adsorption isotherm studies suggest that the capacity, equilibrium constant, and energy of the Cs-Act SB in adsorbing ARS dye are improved compared to Act-SB.